How Does AI Improve Remote Patient Monitoring? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2019)
Remote Patient Monitoring (RPM) is rapidly transforming the healthcare landscape, offering a way to monitor patients' health outside of traditional clinical ...
Keywords: Telemedicine and Digital Health; Improve; Remote; Patient; Artificial Intelligence; Healthcare; Patient Care